Recent advances in halloysite nanotube derived composites for water treatment - Yu, L.; Wang, H.; Zhang, Y.; Zhang, B.; Liu, Jian (2016)
© The Royal Society of Chemistry 2016. Halloysite nanotubes (HNTs) are naturally occurring clay mineral with nanotubular structures and have found increasing potential applications in industrial fields. Here, after a brief introduction of the general structure, main properties and newly emerging applications of HNTs, particular attention is paid to HNT-derived applications in water treatment. We mainly review the recent progress in applications of HNT-derived nanocomposites in heavy metal ion, dye or organic pollutant removal from wastewater and HNT-containing membranes for water filtration. The HNT-derived composites exhibit superior properties for water treatment in various ways and are promising to be used in practical applications. Finally, we summarize the predominant mechanisms acting in the applications of water treatment and future prospects are discussed.